Digestible lysine levels in diets for pigs from 24 to 50 kg under sanitary segregation - Gandra, Érika Rosendo de Sena; Trindade Neto, Messias Alves da; Berto, Dirlei Antonio [UNESP]; Budiño, Fábio Enrique Lemos; Gandra, Jefferson Rodrigues; Schammass, Eliana Aparecida (Sociedade Brasileira de Zootecnia, 2012)
This study evaluated the relationship between digestible lysine and metabolizable energy for barrow and gilts from 24 to 50 kg. Performance, digestibility and blood profile were studied. The experimental design was of randomized blocks, with five treatments, eight replicates and two animals per experimental unit in the performance assay and four replicates and one animal per experimental unit in the digestibility assay. The blood profile was chosen at 20 random animals of each sex, with four replicates per treatment and the animal as experimental unit. The treatments were 0.80, 0.90, 1.00, 1.10 and 1.20% digestible lysine. There was a linear effect of lysine levels on weight gain and feed conversion in females and crude protein in both sexes, gross energy excreted in the urine (kcal) and digestible energy (kcal). A quadratic effect of the amino acid studied in the daily consumption of crude protein (g) in both sexes, weight gain and feed conversion of barrows, as well as the nitrogen excreted in the urine (g) and nitrogen retained, and absorbed and retained. The relationship between neutrophils and lymphocytes had quadratic responses with increasing levels of lysine. The maximum performance for the studied genotype was obtained with 0.88 and 0.91% of digestible lysine or 2.60 and 2.67 g of digestible lysine/Mcal of metabolizable energy for females and barrows, respectively, corrected for digestibility trial.
Keywords: barrow; gilt; leucocytes; metabolizable energy; specific genotype